EDUKASI UNSUR STRATEGI PEMASARAN DALAM PENGEMBANGAN USAHA SAYUR HIDROPONIK - Budi Satria; Dhian Tyas Untari; Timorora Sandha Perdhana; Fata Nidaul Khasanah; Tulus Sukreni; Prasojo Prasojo (Jurnal Pengabdian kepada Masyarakat UBJ, 2022)
The focus in this article is the development of a hydroponic vegetable business. The hydroponic system is well known by the public, in addition to the relatively easy system and application of this system, the grower does not interact with the soil, the hydroponic system is also one of the implementations of the agricultural intensification system. Because the planting rack can be made with a multilevel system, so that with a small area, it can produce quite a lot of plants. The problem faced by hydroponic farmers is the marketing system. Often hydroponic farmers with home scales still have difficulty in marketing their products, the problems are more or less as follows; 1) The operational cost of hydroponic plants is relatively expensive, this affects the selling price. While the general public at the vegetable craftsman only knows conventional vegetables, where the operational costs are relatively cheap and are sold at low prices. So often hydroponic vegetable products cannot compete in price. 2) The market for hydroponic vegetables is in supermarkets, but hydroponic farmers on a home scale with small and relatively unstable production capacity find it difficult to enter supermarkets. These two things are the basis of this writing, which is expected to be a reference for hydroponic farmers in order to optimize existing market opportunities.